First Report of a New Isolate of Metarhizium rileyi from Maize Fields of Quivicán, Cuba - Álvarez, Sandra Pérez; Guerrero, Amaury Méndez; Duarte, Bernardo Nayar Débora; Tapia, Marco Antonio Magallanes; Medina, Jesús Alicia Chávez; Domínguez Rodríguez, Yoannis [UNESP] (Springer Nature, 2018)
Metarhizium rileyi (Farlow) Samson is an important entomopathogenic fungus of more than 30 species of Lepidoptera larvae. The aim of this research was to characterize isolate of M. rileyi from Quivicán, Cuba on the basis of morphological and molecular approaches. The fungus was isolated from samples of S. frugiperda larvae collected from maize fields of Quivicán municipality, Mayabeque province, Cuba, and it was cultured on PDA + Ampicillin solid media for morphological characterization. The DNA was isolated using CTAB method and internal transcribed spacer (ITS1, ITS4) were used as the primers for the amplification. The amplified products of 1335 bp were purified and sequenced at CINVESTAV-IPN in both the directions using the above primers. A consensus sequence was obtained by alignment of the forward and reverse sequences for this region and deposited in GenBank (MG637450). The fungus produced slightly cottony colony of pale green color and dispersed conidia and septal mycelium were observed under the optical microscope. A BLAST search of the sequence in GenBank revealed a 99% of identity with several strains of N. rileyi (e.g., AF368501.1, AB268359.1 and EU553337.1) and M. rileyi (e.g., KY436756.1). This is the first report of M. rileyi isolate from maize fields of Quivicán in Cuba and this is important for biodiversity studies and is another possibility for Integrated Pest Management.
Keywords: Biological control; Entomopathogen fungi; Lepidoptera; Metarhizium rileyi